Abstract - Albrizio R.; Mastrorilli M.; Rana G. (WEMED workshop: how to advance the knowledge on water use efficiency in the Mediterranean region ?, 2007)
Abstracts of ten oral contributions presented to the workshop. It emerges from both papers and these oral contributions that the problem concerning the agricultural use of the water resource in the Mediterranean region is still very debated and far away from a possible solution. Therefore, new research is needed in order to transfer the knowledge from the research environment to the production world. On the other hand, work must be done for improving the comprehension of the water use by the crops at different space scales and more efforts are needed to correctly upscale the results form the plant-crop to the catchment-region level.
Workshop on: How to Advance the Knowledge on Water Use Efficiency in the Mediterranean Region ? 2006/10/26-28, Valenzano (Italy)